THE ROLE OF CORRECTIONAL CENTERS IN OPTIMIZING DIVERSION AS A RESTORATIVE JUSTICE EFFORT IN THE JUVENILE CRIMINAL JUSTICE SYSTEM - Safithri, Hijriyana; Lubis, Ramiah; Qonita, Ra; Sendika, Sendika; Nandita, Riski; Safitri, Hijriyana (Tazir, 2025)
This study examines the Optimization of Diversion as a Restorative Justice Effort in the Juvenile Criminal Justice System which is motivated by the importance of child protection as a legal subject that is still in the development stage. The juvenile criminal justice system in Indonesia through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) regulates the diversion mechanism as an alternative to resolving cases outside the formal judicial channels. Diversion is expected to prevent children from negative stigma, provide opportunities to improve themselves, and restore relationships between perpetrators, victims, and society through the principle of restorative justice. This type of research uses a normative legal approach complemented by field studies. The data of this research was obtained through literature studies in the form of primary, secondary, and tertiary legal materials, and was complemented by primary data through interviews with law enforcement officials and related parties. The analysis technique used is qualitative analysis with an emphasis on synchronization between legal norms and implementation in the field. The results of the study show that the application of diversion in the juvenile criminal justice system still faces several obstacles, such as limited human resources, lack of public understanding of the concept of restorative justice. However, diversion has been proven to have a strategic function in realizing child protection, preventing labeling effects, and supporting children's social reintegration. Therefore, the optimization of diversion can be carried out through strengthening regulations, increasing the capacity of law enforcement officials, and continuous socialization to the community.